Peritoneal implantation of pheochromocytoma – pheochromocytomatosis: a case report and mini review - Bényei, Erik; Laki, András; Kiss, Gergely; Varga, Zsolt; Tóth, Miklós; Tőke, Judit (Frontiers in Endocrinology, 2025)
IntroductionPheochromocytomatosis, defined as the implantation of pheochromocytoma cells to the intraoperatively opened surfaces during surgical manipulation, is an infrequent complication of surgical intervention of pheochromocytomas. Only a handful of pheochromocytomatosis cases have been reported since the first case was described in 2001.Case reportIn 2011, a 33-year-old male patient presented with episodic palpitations and hypertensive surges triggered by physical activity. Imaging revealed a left adrenal tumor, which showed intense radiopharmaceutical uptake on 131I-metaiodobenzylguanidine ([131I]MIBG) scintigraphy. Urinary analysis of metanephrines confirmed pheochromocytoma, and laparoscopic left-sided adrenalectomy was performed. Owing to the large tumor size, intraoperative fragmentation was necessary for removal. The patient remained asymptomatic for five years. In 2016, recurrent paroxysmal symptoms prompted imaging, revealing a lesion at the left renal hilum. During the reoperation in 2017, multiple peritoneal tumor deposits were observed and later confirmed histologically. Over the following years, the patient received conservative, symptomatic treatment with tolerable paroxysmal symptoms. In 2023, worsening symptoms led to the decision to commence three cycles of ([131I]MIBG) therapy, followed by alleviation of symptoms, and a decrease in biochemical parameters.DiscussionAn extensive literature search for publications from the past 25 years identified 22 pheochromocytomatosis cases whose details were also summarized and analyzed. This condition appears to have a longer recurrence-free survival compared to patients’ cohorts with metastatic pheochromocytomas. Pheochromocytomatosis is usually characterized by a prolonged asymptomatic postsurgical interval, emphasizing the need for long-term follow-up with close biochemical and radiological surveillance. Treatment strategies parallel those used for advanced/metastatic pheochromocytomas.